2012
DOI: 10.1093/nar/gks802
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid G-quadruplex structure formed between RNA and DNA explains the extraordinary stability of the mitochondrial R-loop

Abstract: In human mitochondria the transcription machinery generates the RNA primers needed for initiation of DNA replication. A critical feature of the leading-strand origin of mitochondrial DNA replication is a CG-rich element denoted conserved sequence block II (CSB II). During transcription of CSB II, a G-quadruplex structure forms in the nascent RNA, which stimulates transcription termination and primer formation. Previous studies have shown that the newly synthesized primers form a stable and persistent RNA–DNA h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
143
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(148 citation statements)
references
References 31 publications
4
143
1
Order By: Relevance
“…CSB2 is one of three conserved sequence blocks (CSB1-3) located downstream of LSP (124)(125)(126). The CSB2 region is G-rich and during its transcription, a G-quadruplex structure is formed in the nascent RNA, which stimulates transcription termination and the formation of primers that may be used to initiate H-strand DNA synthesis (127,128). The CSB2 region is, therefore, an essential element of O H function.…”
Section: Initiation Of Mtdna Replication At O Hmentioning
confidence: 99%
See 1 more Smart Citation
“…CSB2 is one of three conserved sequence blocks (CSB1-3) located downstream of LSP (124)(125)(126). The CSB2 region is G-rich and during its transcription, a G-quadruplex structure is formed in the nascent RNA, which stimulates transcription termination and the formation of primers that may be used to initiate H-strand DNA synthesis (127,128). The CSB2 region is, therefore, an essential element of O H function.…”
Section: Initiation Of Mtdna Replication At O Hmentioning
confidence: 99%
“…The termination at CSB2 is also stimulated by a poly-dT stretch found just downstream of CSB2. The transcripts remain stably associated with DNA, forming an R-loop structure, and the stability of this structure depends on the formation of a G-quadruplex structure between the nascent DNA and the nontemplate strand (127,128). It appears likely that the prematurely terminated transcripts are used as primers for initiating H-strand mtDNA synthesis because in this region their 3 ends overlap with the transition points from RNA to DNA (126).…”
Section: Regulation Of Mtdna Replication and Copy Number Controlmentioning
confidence: 99%
“…G-quadruplexes formed by RNA result in transcription termination and dictate primer formation for DNA synthesis initiation (77). More recently, Wanrooij et al (78) reported that the mitochondrial RNA primer required for the leading strand origin of mtDNA replication forms a hybrid G-quadruplex between RNA and DNA in CSBII and that this quadruplex formation plays a critical role in determining the rate of DNA synthesis initiation in human mitochondria by influencing the architecture and persistence of an RNA-DNA hybrid (R-loop) residing at the leading strand origin of DNA replication. Because CSBII-like sequences are widespread and found in both yeast and mammals (79) (but not, for example, in Drosophila), G-quadruplexes are now believed to play an important and often evolutionarily conserved role in mitochondrial replication initiation.…”
Section: Mitochondrial Deletions Associated With Potential G-quadruplmentioning
confidence: 99%
“…The Pif1 helicase localizes to G4DNA sequence motifs and binds and unwinds G4DNA structures (13,14). G4DNA is proposed to play specific roles in DNA metabolism including replication (14), gene expression (15), and mitochondrial DNA metabolism (16).…”
mentioning
confidence: 99%